Robotic grasping and manipulation : first Robotic Grasping and Manipulation Challenge, RGMC 2016, held in conjunction with IROS 2016, Daejeon, South Korea, October 10-12, 2016, Revised papers /: first Robotic Grasping and Manipulation Challenge, RGMC 2016, held in conjunction with IROS 2016, Daejeon, South Korea, October 10-12, 2016, Revised papers. (2018) - Unknown
No abstract available